Bhutan : Selected Issues. (IMF Staff Country Reports; Country Report, 1997)
Recent economic developments: economic activity and prices; fiscal developments; monetary policy and developments; external sector developments. Eighth Five-Year Plan; background; objectives and strategy; key elements; and sectoral policies. Financial sector developments and reforms. Statistical tables.